In vitro study on anti-cancer properties of genistein in tongue cancer - Ardito, Fatima (Onco Targets Ther, 2017)
PURPOSE: Tongue cancer is an extremely aggressive disease and is characterized by a poor prognosis. It is a complex disease to treat and current therapies have produced mediocre results with many side effects. Some facts suggest that natural essences can support traditional cancer therapy by carrying out a synergistic function with chemotherapy. Therefore, we evaluated the antitumor effects of genistein on tongue carcinoma cells. METHODS: Genistein 20, 50 and 100 µM were used for 24, 48 and 72 hours on 3 tongue carcinoma cell lines. xCELLigence system was used to evaluate the effects on cell adhesion, proliferation and to calculate IC(50) values. Both MTT assay and Trypan blue assay were used to evaluate alterations in cell viability, scratch assay for cell migration and Western blot analysis for expression of some proteins. RESULTS: Cell adhesion was inhibited especially between 20 and 50 µM of genistein treatment. Proliferation was reduced by 50% for treatments with 20 µM at 24 hours, with 20 or 50 µM at 48 and 50 µM at 72 hours (P<0.0001). Viability tests confirmed a proportional reduction in concentration of genistein and duration of treatments. Even cell migration was reduced significantly (P<0.001). Genistein down-regulates vitronectin, OCT4 and survivin. CONCLUSION: This in vitro study clarifies the anti-tumor effect of genistein on tongue carcinoma. In vivo studies are needed to confirm these data and develop a suitable delivery system that is capable of acting directly on tumor.